Beyond Reward: Insights from Love and Addiction - Andreas J. Fallgatter (Frontiers Research Topics, 2017)
It is an interesting topic to discuss addiction and love in the context of reward. In this e-book, we begin with an animal study of comparison between drug and natural reward. Then, some papers aim to understand the reward system underlying behavioral addiction focusing on technology, for example Internet addiction and mobile phone dependence. The third part of this e-book addresses the topic of love. Considered as a whole, this e-book demonstrates that drug and behavioral addictions are frequently related with negative consequences, while romantic love is related with a positive consequence. That's why romantic love may be considered as a natural addiction. We think that the notion of romantic love as a positive addiction may offer a new view for future research in the field.It is an interesting topic to discuss addiction and love in the context of reward. In this e-book, we begin with an animal study of comparison between drug and natural reward. Then, some papers aim to understand the reward system underlying behavioral addiction focusing on technology, for example Internet addiction and mobile phone dependence. The third part of this e-book addresses the topic of love. Considered as a whole, this e-book demonstrates that drug and behavioral addictions are frequently related with negative consequences, while romantic love is related with a positive consequence. That's why romantic love may be considered as a natural addiction. We think that the notion of romantic love as a positive addiction may offer a new view for future research in the field.